Metode Life History Dalam Menggungkap Penyebab Pilihan Orientasi Seksual Pada Komunitas Gay Di Kota Kendari - Laxmi Laxmi; Raemon Raemon; Erens Koodoh; Sarlan Adi Jaya; Al-Marsaban; La Ode Aris; Zulkifly Zulkifly (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
This research is entitled "Causes of Sexual Orientation Choices in the Gay Community in Kendari City". The aim of this research is to reveal and describe in the life history the causes of sexual orientation choices among gays in Kendari City. There were ten informants for this research, and there were seven informants who were willing to tell in the form of a life history the reasons for being gay. Data collection in this research is direct research in the field using ordinary observation methods, ordinary interviews, and in-depth interviews to search for life history data. The results of this research show that there are several factors that cause them to choose to be gay. Such as the sexual abuse he experienced since childhood, the lack of love he received from his parents, especially his father, the harsh upbringing he received from his parents as a child, and environmental factors, and also past trauma as a victim of sexual violence and abuse.